ADDITION OF FERMENTED Eucheuma cottoni SEAWEED FLOUR WITH FERMENTER EM-4 IN TILAPIA (Oreochromis niloticus) COMMERCIAL FEED - Baiq Sigit Yunita Lestari; Salnida Yuniarti Lumbessy; Zainal Abidin (Jurusan Perikanan dan Kelautan, 2023)
The purpose of this study was to analyze the addition of fermented E cottoni seaweed flour with the EM-4 fermenter in commercial tilapia feed. This research was conducted for 50 days at the Fish Production and Reproduction Laboratory, Faculty of Agriculture, University of Mataram, while for proximate analysis it was carried out at the Laboratory of Nutrition and Animal Feed Sciences, University of Mataram. The research method used was an experimental method with a completely randomized design (CRD), consisting of 4 treatments and 3 replications with the addition of seaweed flour 0%/kg, 10%/kg, 20%/kg, and 30%/kg of commercial feed. Parameters measured were absolute length absolute weight, specific growth rate, feed utilization efficiency ratio (EPP), feed conversion ratio (FCR), survival rate, and water quality. Data were analyzed using the ANOVA test at the 5% level. Then proceed with Duncan's test level of 5%. The results showed that the addition of different concentrations of EM-4 fermented E. cottoni seaweed flour to commercial feeds could affect growth, EPP, and FCR, but did not affect the survival rate of tilapia. The addition of E. cottoni seaweed powder fermented by EM4 at a concentration of 20% could increase the absolute weight, absolute length, specific growth rate, EPP, and FCR of tilapia which were better than the control treatment, which were respectively 7.44 g, 3, 48 cm, 2.31%/day, 93% and 1.2.